THE IMPORTANCE OF PRACTICAL TRAINING IN THE DEVELOPMENT OF AESTHETIC EDUCATION (Academicia Globe: Inderscience Research, 2022)
There are concepts of society and the aesthetic culture of the individual. The aesthetic culture of a society is a set of material and spiritual values that humanity has accumulated throughout history. The aesthetic culture of the child's personality is also the result of his active assimilation of the material heritage of society. Aesthetic culture is constantly changing as a result of the interaction of a person with beauty, as well as the interaction of certain qualities of a person.